Melanin Promotes Spore Production in the Rice Blast Fungus Magnaporthe oryzae - Huang, Pengyun; Cao, Huijuan; Li, Yan; Zhu, Siyi; Wang, Jing; Wang, Qing; Liu, Xiaohong; Lin, Fu-Cheng; Lu, Jianping (Frontiers in Microbiology, 2022)
The rice blast pathogen, Magnaporthe oryzae, spreads through spores and invades rice through appressoria. Melanin is necessary for an appressorium to penetrate plant cells, but there are many unknown aspects of its role in fungal conidiation. In this study, we confirmed that melanin promotes spore production in M. oryzae, and that this effect is related to the background melanin content of wild-type strains. In the wild-type 70-15 strain with low melanin content of aerial hyphae, increased melanin synthesis promoted sporulation. In contrast, increased melanin synthesis in the wild-type Guy11 strain, which has higher melanin content, did not promote sporulation. The transcription factor Cnf1 (conidial production negative regulatory factor 1), which negatively regulates melanin synthesis, has opposite effects in conidiophore differentiation of Guy11 and 70-15. The function of transcription factors Cos1 (conidiophore stalk-less 1) and Hox2 (homeodomain protein 2) in regulating conidiation is not affected by melanin content, while Cnf1, Gcc1 (growth, conidiation and cell wall regulatory factor 1), and Gcf3 (growth and conidiation regulatory factor 3) regulate conidiation by increasing or reducing melanin synthesis. Pig1 (pigment of Magnaporthe 1) regulates the melanin synthesis of hyphae but not of conidiophores, spores, or appressoria. Deletion of the same gene in different wild-type strains can lead to different phenotypes, partly because of differences in melanin content between fungal strains. Overall, this study reveals the functional diversity and complexity of melanin in different M. oryzae strains.